Pengaruh Motivasi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Selatan - Kartika Sandra Desi; Abid Djazuli; Choiriyah Choiriyah (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
The purpose of this study is to determine the effect of work motivation, work discipline and work environment on employee performance the regional parlementary secretariat of South Sumatra Province. The research method used is associative research using random sampling technique using the Issac and Michael formulas obtained by 76 respondents. The SPSS 25 program is used in the analysis technique, which makes use of Instrument Test, Classical Assumption Test and multiple linear regression. Based on the results of the study it is known that work motivation and work discipline have a significant influence on employee performance, work environment does not have a significant effect on employee performance partially. Meanwhile, the variables of Work Motivation, Work Discipline and Work Environment have a significant effect on Employee Performance The Regional Parlementary Secretariat of South Sumatra Province